“MINAT SISWA KELAS X SMAN 12 PEKANBARU MENGIKUTI EKSTRAKURIKULER PRAMUKA” - Riska Anggraini; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted in SMA Negeri 12 Pekanbaru. This research entitled "Student Interest of Class X Sman 12 Pekanbaru Following Extracurricular Scout". The purpose of this research is to know the description of the students' interest in following the scout extracurricular, to know the description of the interest of the male students following the scout extracurricular, To know the description of the interest of the female students following the scout extracurricular, and to know the description of student interest Per Item Following Scout Extracurricular. Data collection tool in the form of questionnaire. Subjects used in this study amounted to 147 people. Determination of sample by using technique of Random Sampling. Data analysis was done by using percentage technique and Pearson product moment correlation. The results showed that general description of student interest, description of interest of male students, description of interest of female students, and description of student's interest per item following scout extracurricular are in high category.Keywords: Student Interest, Extracurricular, Scout